EFEKTIVITAS PROGRAM RUMAH TIDAK LAYAK HUNI (RTLH) BAGI MASYARAKAT TIDAK MAMPU MANUSIA SUKU LAUT DI KABUPATEN LINGGA, PROVINSI KEPULAUAN RIAU - Jannah, Syarifah Mifthahul; Nurlaily, Nurlaily; Situmeang, Ampuan (MIZAN, Jurnal Ilmu Hukum, 2025)
One of the government programs, namely the Uninhabitable House Program (RTLH), aims to improve the standard of living of underprivileged communities, such as the Suku Laut community in Lingga Regency, Riau Islands Province. The purpose of this study is to determine the extent to which the RTLH program has been implemented and how it impacts the welfare of the Suku Laut community. By using semi-structured interview techniques, document analysis, and observation, an empirical legal research methodology is used. The research employs an empirical legal research method, utilizing semi-structured interviews, observations, and document studies as techniques. The findings indicate that the RTLH program has contributed to improvements in housing conditions, health, and access to basic facilities. However, challenges were identified in program implementation, such as uneven aid distribution and logistical issues that affect overall program effectiveness. Therefore, it is recommended that improvements be made in planning, transparency, and periodic evaluation to ensure that the program's benefits are comprehensively and sustainably experienced by the community.